Electrochemical Studies Of Tetrathiafulvalene, 7,7,8,8 Tetracyanoquinodimethane And Their Mixture - Ng, Geok Koon (2003)
Cyclic voltammetry (CV) and Chronoapmerometry (CA) were employed to study the electrochemical oxidation of microcrystalline tetrathiafulvalene (TTF) attached mechanically to the surface of a glassy carbon electrode and immersed in 1 M KBr solution. The effect of temperature, electrolyte concentration and scan rate were been examined. Multiple cycling (CV) was carried out to examine the reproducibility and stability of the redox materials generated at the electrode surface. Change in particle sizes of the oxidized TTF compound was examined by scanning electron microscopy (SEM). Detection of non-monotonic rising current transient in Chronoamperometric data, a small maximum observed at cross-over of scan reversal into the anodic or cathodic wave and the presence of a large inert zone (hysterisis) even at low scan rate during cyclic voltammetry as well as the electrode microscopy result are evidence of the nucleation and growth process occurring at the electrode-solid-electrolyte interfaces. Similar results and evidences obtained during electrochemical studies of TTF -TCNQ mixture compound.